Forest as carbon land for ecological sustainability - Abhishek Raj; MK Jhariya (Global Journal of Ecology - Peertechz Publications, 2020)
Currently 4.70 million ha of forest area lost every year during a decade of 2010-20 which is less than 7.8 million ha yr-1 in the 1990s [1]. The loss of forest areas are also reported as 98 million ha due to fires in the year 2015. Similarly, around 301 million ha (7.0 %) areas of natural regenerating forest are decreased over the past 30 years [2]. Deforestation contributed approx 20 percent of total green house gas emissions which is more as compared to industrial and transport emissions. Around 2.8 gigaton of carbon removal per year has been observed due to deforestation [3].